The role of the Inflammatory Cytokine Interleukin-6 (IL-6) in moderating the relationship between pesticide exposure and metabolic syndrome in vegetable farmers - Bibit Nasrokhatun Diniah; Sulistiyani Sulistiyani; Tri Joko; Budiyono Budiyono (Journal of Public Health and Development, 2026)
Pesticide exposure has been associated with metabolic syndrome (MetS). However, the moderating role of inflammatory cytokines, such as interleukin-6 (IL-6), remains unclear. This study examined how IL-6 moderates the relationship between acetylcholinesterase (AChE) activity, as a pesticide-exposure biomarker, and the risk of MetS among vegetable farmers. We conducted a case–control study involving 134 male farmers (44 MetS cases and 90 controls) selected from a 13-week population screening of 307 farmers in Kuningan, West Java from January to May 2025. Exposure was assessed through the measurement of acetylcholinesterase (AChE) activity, while IL-6 served as an inflammatory biomarker. MetS was diagnosed according to the International Diabetes Federation criteria. Venous blood samples were collected twice for AChE analysis and once for IL-6 measurement. Moderation analysis using linear regression with the PROCESS Macro SPSS revealed that IL-6 significantly moderated the effect of AChE on waist circumference (WC), systolic and diastolic blood pressure (BP), and MetS. The conditional effect of AChE on MetS according to IL-6 values increased with high inflammation (B = 0.0031, p = 0.0004 for WC; B = 0.0059, p = 0.0008 for systolic BP; B = 0.0027, p = 0.0064 for diastolic BP; and B =-0.0009, p = 0.0041 for MetS). Scatter plot patterns further supported the biological plausibility of this moderating mechanism. IL-6 modifies the strength and direction of the inflammatory response, enhancing the impact of pesticide exposure on key MetS components. These results underscore the central role of IL-6 in the cholinergic pathway and indicate that lowering chronic low-dose pesticide exposure may reduce inflammation-related metabolic risks.